Low lung function in Bipolar Disorder and Schizophrenia: a hidden risk - Ruiz-Rull, Cristina; Jaén-Moreno, María José; del Pozo, Gloria Isabel; Gómez, Cristina; Montiel, Francisco Javier; Alcántara, Montserrat; Carrión, Laura; Chauca, Geli Marie; Feu, Nuria; Guler, Ipek; Rico-Villademoros, Fernando; Camacho-Rodríguez, Cristina; et al. (Frontiers in Physiology, 2024)
Introduction: People with serious mental illness (SMI), such as schizophrenia and bipolar disorder, have a higher risk of premature morbidity and mortality. In the general population, impaired lung function is associated with increased morbidity and mortality. We compared lung function between people with and without serious mental illnesses using a cross-sectional study in 9 community mental health units.Methods: Subjects aged 40-70 years with a diagnosis of schizophrenia or bipolar disorder were recruited consecutively. The controls had no psychiatric diagnosis and were not receiving any psychotropics. Spirometry was performed by a trained nurse. We used the 2021American Thoracic Society/European Respiratory Society standards for the interpretation of the spirometry results.We studied 287 subjects. People with SMI (n=169) had lower spirometry values than those without a psychiatric diagnosis (n=118). An abnormal spirometry pattern (36.1% vs. 16.9%, p<0.001), possible restriction or non-specific (Preserved Ratio Impaired Spirometry [PRISm]) pattern (17.8% vs. 7.6%, p=0.014), and pattern of airflow obstruction or possible mixed disorder (18.3% vs. 9.3%, p=0.033) were more frequent in people with SMI. Multivariate analyses showed that the PRISm pattern was associated with abdominal circumference (odds ratio [OR] 1.05, 95%CI 1.03 to 1.08) and that the pattern of airflow obstruction or possible mixed disorder was associated with smoking behavior (OR 5.15, 95%CI 2.06 to 15.7).People with SMI have impaired lung function, with up to one-third of them showing an abnormal spirometry pattern. This suggests that regular monitoring of lung function and addressing modifiable risk factors, such as tobacco use and obesity, in this population is of paramount importance.